Compressive properties of nanosilica filled epoxy polymers and hybrid fibres composite laminates / Norhafiza Muhammad - Muhammad, Norhafiza (2015)
Epoxy and fibre exhibit brittle behaviour that contribute to low matrix dominated properties such as compressive strength and shear strength of the composites. The compressive strength (CS) of FRP composites is usually less than tensile strength and may reduce by more than 50% due to the presence of stress raisers for instance fastener holes and notches. Therefore CS is one of the main important considerations in designing composite structure. The addition of nano-sized fillers into the epoxy (called nanomodified-epoxy) can lead to a number of desirable effects. The aim of this research is to evaluate the effect of nanosilica on the compressive properties of Carbon fibre reinforced polymer composites (CFRP), Glass fibre reinforced polymer composites (GFRP), Kevlar fibre reinforced polymer composites (KFRP) and Hybrid fibres reinforced polymer composites. A series of nanosilica filled epoxy polymer was fabricated using 5wt%, 13wt% and 25wt% nanosilica contents. This modified resin was used to manufacture FRP composite laminates. This thesis comprises of two main parts which are characterization of the nanosilica filled polymer and investigation on compressive properties of the nanosilica-FRP composites. In the first part, experimental investigations were conducted in order to identify the degree of dispersion of nanosilica in the resin system and analyse the physical properties of polymer. In the second part, the effect of nanomodified epoxy on the mechanical properties of FRP composite was studied. The composite laminates were fabricated using vacuum bagging techniques. It was found that the nanonosilica particles were homogeneously distributed in the epoxy and no agglomeration was observed even at the the highest nanosilica content of 25 wt%. The results showed that the inclusion of 25wt.% nanosilica into the polymer significantly enhanced the compression strength and modulus of about 50% and 108%, respectively, when compared to the pure polymer. The addition of nanosilica improved the compressive properties of all FRP systems, CFRP, GFRP, KFRP and Hybrid composites, without any significant reduction in failure strain. For hybrid composite system, placing carbon woven cloth layers in the exterior and Kevlar woven cloth in the interior gives higher compressive strength than placing glass woven cloth layers in the exterior and Kevlar woven cloth in the interior.